Factor Analysis Factors related to the Implementation of Patient Handovers in Hospitals: systematic literature review - Ali Ali; Yufitriana Amir; Sri Wahyuni (PT. Anagata Sembagi Education, 2025)
Patient Handover is an important process in healthcare that serves to ensure continuity of care and prevent medical errors. This study aims to analyze the factors associated with the implementation of patient handover in hospitals through a systematic review of various relevant literature. The results of the analysis showed that some of the main factors that affect the effectiveness of handover include the level of education and experience of nurses, motivation and job satisfaction, effective supervision by the head nurse, as well as organizational policies that support patient safety culture. In addition, the use of structured protocols, such as checklists and standardized formats, has been shown to improve the accuracy of information delivered in handovers. However, the study also identified various challenges, including time pressure, high workload, as well as a lack of communication training for health workers. Therefore, a comprehensive strategy is needed that includes increasing the competence of nurses, strengthening hospital policies, and optimizing the use of technology to support the handover process. Implementation of these measures is expected to improve patient safety and quality of health care in hospitals.